The Effectiveness of the Game-Based Learning Model in Improving Students’ Critical Thinking Skills - Shelly Morin; Ayu Agustianingsih (IQRO: Journal of Islamic Education, 2026)
This study aims to analyze the effect of applying the Game Based Learning (GBL) model assisted by Wordwall on improving students' mathematical critical thinking ability, considering students' learning styles. The study used a quasi-experimental design with two groups: an experimental class using the GBL model assisted by Wordwall, and a control class using conventional learning methods. The research sample consisted of seventh-grade students at SMP Negeri Jakarta, classified into visual, auditory, and kinesthetic learning styles. Instruments included mathematical critical thinking tests (pretest and posttest) and a learning style questionnaire. Data were analyzed using two-way ANOVA with SPSS 26. Results showed: (1) no significant difference in mathematical critical thinking based on learning style (sig. = 0.227); (2) a significant difference in mathematical critical thinking between the GBL and conventional classes (sig. = 0.000, F = 24.351); (3) no interaction between learning style and learning model (sig. = 0.499). The N-Gain of the experimental class was higher than the conventional class, demonstrating the effectiveness of GBL assisted by Wordwall in improving students' mathematical critical thinking ability.